Adoption as adaptation: Household decision making and changing rural livelihoods in Lombok, Indonesia. (January 2022) - Williams, Liana J.; van Wensveen, Monica; Dahlanuddin,; Grünbühel, Clemens M.; Puspadi, Ketut
Abstract: In agricultural research for development adoption of new technology tends to be cast in categories: adoption, partial adoption, dis-adoption or non-adoption. While these may serve for pragmatic classification and measures for project success or impact they fail to properly acknowledge the ongoing and independent efforts of farmers (and others) in experimentation and integration of knowledge across a range of sources. This paper explores responses to practices for cattle management introduced during a research project, at project close, and five years after the project has finished. We consider the perceptions and application of new knowledge by farmers, extension staff, and policy makers. By taking a longer-term view, we demonstrate how farming households adapt and integrate knowledge from different sources into their daily practice, influenced by local institutions and changing cultural expectations, as well as external researchers. We also consider the influence of changing government priorities and incentives in steering farm-management decisions. Results suggest that a focus on measures to build capacity and empower farmers with information to adapt and respond to change, regardless of project activities, is a much more important goal and indicator of impact than measuring adoption. Highlights: Considers household decision making process for 'adoption' of new technology. Analysis years after interventions finish show ongoing farmer adaptation of practices. Enabling long-term change requires alignment with policy across scales. A focus on capacity building, rather than adoption, will be more impactful over time.